Metodologija i postupak izradbe studije izvodljivosti cestovnih prometnica- čimbenik racionalne investicijske politike - Šimulčik, Damir (Promet - Traffic&Transportation, 2012)
A rational investment policy in market economy is absolutely rooted in scientifically established and accepted methodology and elaboration procedure. Based upon this kind of assessment it shall furnish highest guarantees for rationalization of loan funds pumped into the investment project. The paper deals with the effectiveness of the procedure of elaboration of the feasibility study because unless provided it would make impossible the implementation of a rational investment policy, within the framework of the market system of doing business. A series of methodological procedures being the basic elements of investment activities have been accentuated. In this, major import is assigned to a prospective investor given a wider scope of responsibilities considering the funds spent as an independent factor in the process of doing business and repayment of the negotiated loan.